A convergence formula for sound transmission loss of composite laminates based on three different shear deformation theories - Zhang Zhihao; Ye Renchuan; Ji Ming; Zhu Guoliang (Acta Acustica)
The Classical Plate Theory (CPT), First-order Shear Deformation Theory (FSDT), and Third-order Shear Deformation Theory (TSDT) have been widely applied in analyzing the Sound Transmission Loss (STL) of composite laminates. However, there are no accurate criteria or formulas to determine the convergence criterion in the process of sound transmission loss analysis. The current method for determining convergence is based on assessing a few typical frequencies to judge convergence across the entire frequency range, resulting in inaccuracies in the high-frequency region and wasting significant computational resources. To address this issue, this paper proposes a new convergence criterion and formula based on CPT, FSDT, and TSDT. These formulas provide a precise framework for determining the optimal number of modes required for convergence, ensuring computational efficiency and accuracy in STL calculations for composite laminates across all frequency ranges.